The Moderating Effect of Brand Architecture on the Relationship Between Responsiveness and Customer Loyalty Among Telephone Mobile Subscribers in Kenya - Kwamboka, Metobo Joseline; Sulo, Timothy; Korir, Michael (European Scientific Journal, ESJ, 2017)
The brand architecture of an organization enables customers to enjoy a wide range of services by the same service giver. The purpose of this study was to assess the moderating effect of brand architecture on the relationship between responsiveness and customer loyalty in the mobile telecommunications industry in Kenya. The objectives of the study were to establish the effect of responsiveness on customer loyalty and to find out the moderating effect of brand architecture on the relationship between responsiveness and customer loyalty. An explanatory survey design which is a quantitative research design was adopted. The theory of reasoned action guided the study. The subscribers of the four telecom mobile providers, (Safaricom, Airtel, Telecom Kenya Limited (Orange), and Essar (YU), in Eldoret Town (Western Kenya) were targeted. They totaled over 306,683. A sample size of 500 respondents was selected using stratified and systematic sampling which are probability sampling designs. Questionnaires with Likert scale questions were used to collect data. Multiple regression and Hierarchical moderated regression analysis were used for data analysis. Before brand architecture was introduced into the relationship, it was established that responsiveness determines customer loyalty of mobile subscribers of telecom mobile providers as the four items used had a significant effect on customer loyalty. After the introduction of brand architecture into the relationship it was established that there was both a positive effect and a negative effect. Only one item had a significant effect on customer loyalty. While deciding on offering more services to the subscribers, the telecom mobile providers should know that the relationship between their responsiveness and customer loyalty will change.